"Phobie à deux" and other reasons why clinicians do not apply exposure with response prevention in patients with obsessive–compulsive disorder. Issue 2 (4th March 2019) - Moritz, Steffen; Külz, Anne; Voderholzer, Ulrich; Hillebrand, Thomas; McKay, Dean; Jelinek, Lena
ABSTRACT: Meta-analyses suggest that exposure with response prevention (ERP) is the most efficacious treatment for obsessive–compulsive disorder (OCD) and treatment guidelines for the disorder accordingly recommend ERP. Despite this, many therapists, including those with a cognitive-behavioral therapeutic background, do not perform ERP in patients with OCD. The present study aimed to elucidate the reasons why. German therapists ( N  = 216) completed an anonymous online survey, the newly developed Reasons for Not Performing Exposure in OCD Scale (REPEX), that inquired whether, to what extent, and how they perform ERP in the treatment of OCD. We also asked their reasons for not applying ERP in the past. Most therapists considered ERP an efficient treatment for OCD. Marked differences emerged between physicians and psychologists, however. The former used exposure less often and for a shorter period, preferred in sensu to in vivo exposure, and conducted exposure less often in the personal environment of the patient than did psychologists. Both groups were familiar with clinical guidelines to a similar extent. A factor analysis of the REPEX scale revealed five factors. Patient lack of motivation, preference for exposure to be self-help as well as alleged organizational difficulties were endorsed most often. The latter was correlated with the age of the therapist and was far more often affirmed by physicians. Fear of side effects was named by a subgroup of clinicians; in the context of patient ambivalence, this may foster "phobie à deux". Unlike prior research, lack of expertise was rarely identified as a reason not to use ERP. Recommendations for improving adherence to guidelines are discussed.